Effect of Moringa Oliefera Supplementation During Pregnancy on Stunting in Children of Pre-School Age - Hasan Basri; Nur Hikmah; Veni Hadju; Burhanuddin Bahar; Andi Zulkifli; Syamsiar S. Russeng (Jurnal Kesehatan Masyarakat, 2025)
Stunting is a growth failure due to a lack of nutrition that has lasted from pregnancy to 24 months of age. This study aims to examine the effect of moringa supplementation during pregnancy on stunting in preschool children (5-6 years old). This study is a follow-up study of a Randomized Control Trial with Double Blind study that provides moringa supplements in the form of PG (Powder Group), EG (Extract Group), and as well as IFA (Iron Folate Acid) supplements to pregnant women. The subjects were 303 children in six sub-districts in Jeneponto District who were children of mothers who received supplementation of PG, EG, and IFA during pregnancy. Children’s height was measured using a microtoice. Data were statistically analyzed using the Logistic Regression test. The results showed a significant difference between the three groups. EG intervention had a significant effect on stunting in preschool-age children (5-6 years old). EG intervention (24.18%) showed the lowest prevalence of stunting among PG (25.47) and IFA (38.68%) interventions. EG prevented stunting by 2.215 times compared to the other intervention groups. The provision of Moringa extract to pregnant women has a better effect on reducing stunting.